KOMUNIKASI ANTARPRIBADI JARAK JAUH ANTARA ORANGTUA DAN ANAK (Studi Pada Mahasiswa Universitas Riau Yang Berasal Dari Kabupaten Rokan Hulu) - Vani Rasika; Evawani Elysa Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Interpersonal communication between parentas and children is an important role in enhancing the self discipline of children as a person of character. When parents separate of distance with their children, thay have to communicate with their children whom is very difficult to controll them when children still lived with them. There are problems that caused by lack of parental supervision due to children can’t control their deviant behavior. This research is done for determining the effectiveness of long dictance’s interpersonal communication between parents and children as well long distance’s communication media which used University of Riau’s student whom are in Rokan Hulu.This research used qualitative methode with research’s location in Rokan Hulu. The subject of research is 10 parents and 10 University of Riau’s students whom selected by purposive technique. In order to obtain the data, the researcher used three kinds of data collection techniques, such as participant observation, in-depth interview, and documentation.The result of research showed the first, that the effectiveness of long distance’s interpersonal communication between parents and children (study of University of Riau’s students whom lives in Rokan Hulu), there is openess that shown by parents rather than children; then deeply empathy that felt by parents to children rather than children to parents; and being supportive (supportivennes) parents whom make children feel spirit and always remember their parentss’ advices; then a positive attitude (positivennes) of parents when giving the children confidence and showing affection to the children; and the last equality attitude to be fair among the children and give the freedom to the children in making a opinion. Second, this long distance’s interpersonal communication used the visual communication media such as cell phone. Then the media used audiio visual’s media and social networks such as facebook and blackberry massanger or BBM.Keywords: interpersonal communication, effectiveness of interpersonal communication, long-distance relationships between parents and children, juvenile delinquency